Firm characteristics and the cyclicality of R&D investments - Spyros Arvanitis; Martin Woerter (ETH Zurich, KOF Swiss Economic Institute, 2011)
Aim of this study is to combine micro-aspects of firm behaviour with macro-aspects of business development and identify market conditions (for example, price competition) and firm characteristics (for example, type of R&D partners) that enable a firm to have a procyclical, anti-cyclical or non-systematic R&D investment behaviour. New elements of our analysis are: (a) the identification in our data of the above three main types of R&D behaviour with respect to the fluctuation of overall economic activity as measured by a standard composite indicator of the business conditions at industry level and (b) the investigation of a series of hypotheses as to innovation-relevant firm characteristics that underline the three different behaviour categories. The empirical results confirm to large extent our hypotheses and allow us to make profiles of the three types of R&D behaviour.
Keywords: O3; 330; R&D; anti-cyclical behaviour; pro-cyclical behaviour